Effect of nursing care regarding postoperative complications among diabetic patients after hip replacement surgery - Mohammed Tariq; Munther Natheer; Rami Ramadhan Allo (Medical Journal of Babylon, 2023)
Background: The total hip arthroplasty surgery is an effectiveness intervention to improve patients function with osteoarthritis. This surgery is usually done for patients who aged more than 60 years and are associated with uncontrolled pain or hopeless damage hip joints. The effect of diabetes disease at post-surgical time, influencing on wounds healing process and promoting sores formation which lead to a complex of nursing care performance for patients has a big challenge, to deal with patients and their family feeling to help them to promote independence. Objective: This study aimed to evaluate the nursing management for diabetic patients undergoing surgical total hip replacement. Materials and Methods: A case–control study design applied on diabetic patients with a hip operation after fractured hip at orthopedic wards at Al-Rabea and Ninevah private hospitals in Mosul city. The study was conducted from September 10, 2022 until December 10, 2022. Postoperative nursing care provided to the control group was the daily common nursing care management in our hospitals, whereas that provided to the study group depended on a special standard nursing care management protocol. Results: Evaluation of postoperative disorders and complications showed a positive direction in decreasing their occurrence after depending on a special standard nursing care management protocol. Conclusions: The study concludes that all the postoperative complication may be relieved after total hip replacement as any surgical intervention if the orthopedic nursing staff applied the standard tool for nursing care management.